Resposta a inoculação de bactérias diazotróficas associada e não à adubação nitrogenada em trigo (Triticum aestivum L.) - Genero, Jésica Fernanda de Souza (2016)
The bacteria Azospirillum brasilense and Herbaspirillum seropedicae are nitrogen fixers and promoting plant growth, able to promote partnerships with the trigo. O objective of this study was to evaluate the crop wheat agronomic performance in response to inoculation with Azospirillum brasilense diazotrophs and Herbaspirillum seropedicae with or without nitrogen fertilization and quantify the number of viable cells of bacteria of the wheat plant roots. The experiment was conducted in the crop year 2014/2014 and 2015/2015. The experimental design was a randomized block in factorial 2 x 4, with four repetitions. The first factor relates to the nitrogen topdressing applications (with and without nitrogen). The second factor relates to inoculating seeds with diazotrophs [without inoculation treatment (control), strain A. brasilense, H. seropedicae strain and combination of the two strains. The combined inoculation of strains A. brasilense + H. seropedicae with nitrogen fertilization promoted an increase of 48% and 13% in grain yield, in the 2014 season and 2015 season, respectively, for the plants that were not inoculated. You can check the inoculation Herbaspirillum, showed better total amount of viable cells with the application of nitrogen. The reduction in the number of CFU of Azospirillum under nitrogen fertilization condition can point to a lower competitiveness of these individuals by exudates and nutrients